EFEKTIVITAS MODEL PELATIHAN PARENTING AUTISME BERBASIS MEDIA VIDEO - Edi Purnomo; Putut Wijayanto (Kwangsan: Jurnal Teknologi Pendidikan, 2018)
This research aims to; (1) to know the effectiveness of video-based autism parenting training implementation in improving the cognitive skills of trainees; (2) obtaining information about learners' response towards video-based autism parenting training. The method used in this research is Pre-Experimental Design method with One Groups Pretest-Posttest Design, that is research design by pretest before training and posttest after training. The results show that video-based autism parenting training is very effective to improve the cognitive skills of trainees in terms of parenting for autism. The conclusions of this research are: (1) Video-based autism parenting training proven effective in improving cognitive skill of trainees. (2) the trainee's response to the training model based on instructional video media showed a positive response. The results of this research are useful to be implemented in similar training in the future. AbstrakPenelitian ini bertujuan untuk; (1) mengetahui efektivitas pelaksanaan pelatihan parenting autisme berbasis media video dalam meningkatkan keterampilan kognitif peserta pelatihan; (2) memperoleh informasi mengenai respon pebelajar terhadap pelatihan parenting autisme berbasis media video. Metode yang digunakan dalam penelitian ini adalah metode Pre-Experimental Design dengan One Groups Pretest-Posttest Design, yaitu desain penelitian yang terdapat pretes sebelum diberi perlakuan dan postes setelah diberi perlakuan. Hasil penelitian menunjukkan bahwa pelatihan parenting autisme berbasis media video sangat efektif untuk meningkatkan keterampilan kognitif peserta pelatihan dalam hal parenting autisme. Kesimpulan dari penelitian ini, yaitu: (1) Pelatihan parenting autisme berbasis media video terbukti efektif meningkatkan keterampilan kognitif peserta pelatihan. (2) respon peserta pelatihan terhadap model pelatihan berbasis media video pembelajaran menunjukkan respon positif.